Towards a New Partnership for Inclusive Growth in the Middle East and North Africa - World Bank (Washington, DC, 2012)
Citizens are challenging authorities across the Middle East and North Africa (MENA), in countries with diverse socioeconomic and institutional settings. From wealthy Bahrain to impoverished Yemen, from Tunisia with its sophisticated state institutions, to Egypt with its five thousand years of culture and civilization, the unifying refrain has been 'dignity, respect and freedom' and an end to the Arab exceptionalism which has denied rights enjoyed elsewhere. The Arab spring in the spirit of a popular awakening has arrived. This brief proposes a framework for support to MENA based on the four building blocks, which are closely interconnected. Support to the region could address the four development priorities under the overall approach that policy is as important as money.